PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP BUDAYA ORGANISASI, MOTIVASI KERJA, KOMITMEN OGANISASIONAL DAN KINERJA KARYAWAN (Studi Pada Pegawai Rumah Sakit Muhammadiyah Ahmad Dahlan, Kediri ) - Ida Siswatiningsih; Kusdi Raharjo; Arik Prasetya (University of Merdeka Malang, 2016)
The purposes of this study are: to examine the influence of transformational leadership and Transactional leadership towards organizational culture, motivation, organizational commitment, and employee performance. Place of research carried out in Muhammadiyah hospital of Ahmad Dahlan Kediri, consists of 353 staff. The study sample derived from questionnaire have distributed include 130 respondents covering 81 people (62%) health workers and 49 people (38%) non health personnel / administrative personnel. Statistical analysis technique by Structural Equation Model (SEM) and different test. The hypothesis testing results show that: (1) Transformational leadership has a positive and significant impact towards organizational culture and organizational commitment. (2) Transactional leadership has a positive and significant impact towards organizational culture and employee performance);(3) organizational culture has a positive and significant impact towards motivation; (4) Motivation has a positive and significant effect towards organizational commitment; (5) Organizational commitment positively and significantly influence employee performance; (6) Transformational leadership has a positive but not significant effect towards motivation and employee performance;(7) Transactional leadership has a positive but not significant effect towards motivation and organizational commitment.